The Effects of Smart Diplomacy on the Ease, Speed and Accuracy of Political Communication in the International System (Tikrit Journal For Political Science, 2023)
For the first time in 2009, the term smart diplomacy entered the world political literature by Hillary Clinton, the last US Secretary of State. In fact, smart diplomacy is the result of synergy between hard power and soft power, hard threat and soft threat, and hard security and soft security. In fact, by using this new diplomacy, governments will have all types of diplomacy such as cyber diplomacy, media diplomacy, digital diplomacy, sports diplomacy, parliamentary diplomacy, etc. This research has been done with descriptive-analytical method and using available documents. According to the results of smart diplomacy using all dimensions of diplomacy and moral and financial capacity to help deal with the current era. Smart diplomacy has had positive effects in the ease, speed and accuracy of political communication and of course international influence. By using this type of diplomacy, governments, as the main players in the international arena, have a high speed in making decisions about the amount of tools and information provided, and are currently implementing decisions with great care.
Keywords: • Smart diplomacy • Political communication • International system